2005
DOI: 10.1021/jp045519m
|View full text |Cite
|
Sign up to set email alerts
|

Far- and Mid-Infrared of Crystalline 2,2‘-Bithiophene:  Ab Initio Analysis and Comparison with Infrared Response

Abstract: Infrared intramolecular vibrations and lattice modes in the crystalline phase of 2,2'-bithiophene (2T) are investigated using the direct method combined with density functional theory (DFT)-based total energy calculations. For the first time, the far- and mid-infrared responses have been calculated from the Gamma-point modes and the Born effective charge tensors of the 2T crystalline phase. The relative good agreement between the calculated and experimental infrared spectra allows us to assign the origin of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 21 publications
6
40
0
Order By: Relevance
“…The second frequency range is mainly dominated by thiophene phonon modes. These proposed assignments are consistent with those reported in the literature on oligothiophenes 16,20,40,39,41 and oligophenylenes. 21,[26][27][28] …”
Section: Phonon Mode Assignmentssupporting
confidence: 91%
“…The second frequency range is mainly dominated by thiophene phonon modes. These proposed assignments are consistent with those reported in the literature on oligothiophenes 16,20,40,39,41 and oligophenylenes. 21,[26][27][28] …”
Section: Phonon Mode Assignmentssupporting
confidence: 91%
“…24−27 For example, the calculation of THz phonon modes of the oligothiophene crystal 2,2′-bithiophene, which is hereafter noted as "BT", performed by Hermet et al 27 showed a relatively good agreement with the experimental data. However, the calculated THz phonon modes appear somewhat complicated and are still not exactly agreeing with the experimental observations.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Recently, this work has been completed with success to the far-and mid-infrared simulations on the LT and HT polymorph phases of 4T in order to understand in more detail polymorphism on the experimental infrared spectra of this material. 29 …”
mentioning
confidence: 99%